Laughter and SEFT therapy for disaster survivors in Cianjur District - Lely Ika Mariyati; Ghozali Rusyid Affandi; Hazim Hazim; Gandhy Putra Prawira; Faridatul Amaliyah; Arliska Putri Arianti (Universitas Muhammadiyah Magelang, 2023)
An earthquake with a magnitude of 5.6 struck Cianjur Regency, West Java, affecting 12 sub-districts. This earthquake caused significant damage, impacting a total of 114,683 people, resulting in 338 fatalities, 5 missing individuals, hundreds of injuries, and extensive property damage. It also led to mental health issues among survivors, stemming from the loss of family members and property. The objective of this community service activity is to provide psychological intervention to earthquake survivors in Cariu village, Mangunkerta village, Cianjur, through laughter therapy and Spiritual Emotional Freedom Technique (SEFT). The activity is structured into three stages, 1) preparation, 2) delivering laughter and SEFT therapy, and 3) evaluation encompasses post-tests and interviews to assess the impact of the intervention.The results of this psychological intervention initiative demonstrated a significant reduction in symptoms of anxiety (neurosis) and a decrease in the number of survivors experiencing post-traumatic stress (PTSD). However, there is a continued need to monitor survivors who may still be dealing with anxiety disorders, despite their participation in laughter therapy and SEFT.